Immigration and Preferences for Redistribution in Europe - Alberto Alesina; Elie Murard; Hillel Rapoport (Institute of Labor Economics (IZA), 2019)
We examine the relationship between immigration and attitudes toward redistribution using a newly assembled data set of immigrant stocks for 140 regions of 16 Western European countries. Exploiting within-country variations in the share of immigrants at the regional level, we find that native respondents display lower support for redistribution when the share of immigrants in their residence region is higher. This negative association is driven by regions of countries with relatively large Welfare States and by respondents at the center or at the right of the political spectrum. The effects are also stronger when immigrants originate from Middle-Eastern countries, are less skilled than natives, and experience more residential segregation. These results are unlikely to be driven by immigrants' endogenous location choices.
Keywords: D31; D64; I3; Z13; 330; income redistribution; population heterogeneity; welfare systems; immigration